2012
DOI: 10.1111/j.1365-2516.2012.02810.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion in haemophilia: current practice in Europe

Abstract: Summary. Continuous infusion (CI) of factor VIII (FVIII) is an effective method for replacement therapy in haemophilia. Recently, concerns have been raised regarding association of CI with the development of inhibitors. The aim of this study was to gain information on the current practices in Europe regarding CI and the true inhibitor incidence after this mode of therapy. In a cross sectional study performed in 22 Comprehensive Care Centres (CCCs), we evaluated CI techniques, treatment protocols, efficacy, saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 62 publications
(114 reference statements)
1
40
1
2
Order By: Relevance
“…KI je posebej varen način nadomestnega zdravljenja, saj z njo vzdržujemo stalne aktivnosti FVIII / IX in znižamo celokupno porabo faktorja. S KI se izognemo nepotrebnim občasnim previsokim, tudi lahko nevarnim aktivnostim faktorja, poleg tega pa očistek strjevalnega faktorja v prvih dneh KI pomembno pade (51)(52)(53)(54)(55)(56)(57). V nasprotju z nekdanjim mnenjem pa danes izkušnje velikih centrov dokazujejo, da KI pri tež-ki in lahki obliki HA ne sproži pogostejše tvorbe inhibitorjev (55,58,59).…”
Section: Kontinuirana Infuzija Fviii / IXunclassified
“…KI je posebej varen način nadomestnega zdravljenja, saj z njo vzdržujemo stalne aktivnosti FVIII / IX in znižamo celokupno porabo faktorja. S KI se izognemo nepotrebnim občasnim previsokim, tudi lahko nevarnim aktivnostim faktorja, poleg tega pa očistek strjevalnega faktorja v prvih dneh KI pomembno pade (51)(52)(53)(54)(55)(56)(57). V nasprotju z nekdanjim mnenjem pa danes izkušnje velikih centrov dokazujejo, da KI pri tež-ki in lahki obliki HA ne sproži pogostejše tvorbe inhibitorjev (55,58,59).…”
Section: Kontinuirana Infuzija Fviii / IXunclassified
“…This issue is of particular interest and concern for patients with milder forms of the disease not heavily exposed to the factor. In most studies, however, both continuous infusion and bolus injections have been used, and in some large centers significant numbers of patients have been treated with continuous infusion with no indication of an increased incidence of inhibitors [42]. Therefore, at least in patients with severe disease, there appears to be no evidence on which to base a recommendation that continuous infusion should be avoided and from a logical point of view the same should be true for those with a milder form.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Continuous infusion of factor VIII Continuous infusion using a variety of pdFVIII and rFVIII products has been introduced into common practise of hemophilia management worldwide, with 61% and 59% of comprehensive care centers employing CI in the US and Europe, respectively [19,20,24]. The Japanese guideline for hemophilia treatment suggest to use CI for major surgery [35,36].…”
Section: Prevention Of Thrombophlebitismentioning
confidence: 99%
“…Most recently Takedani [37], Rahmé et al [38], and Chevalier et al [39] reported on successful use of CI in 28, 20, and 72 total knee replacements, respectively. A prospective controlled study comparing CI and BI for major surgery using protocols that were similar regarding the surgical technique and postoperative target minimum levels demonstrated that efficacy and safety were better with CI than with BI in terms of minimum factor levels achieved, blood loss (as measured by a decrease in hemoglobin level), blood transfusion requirements, and bleeding complications ( [24]. The incidence of postoperative bleeding among the centers was only 1.8% (range 0-7.0%).…”
Section: Prevention Of Thrombophlebitismentioning
confidence: 99%
See 1 more Smart Citation